An update on Hutchinson-Gilford progeria syndrome: a review of the current state of knowledge in Genetic Etiology, Molecular Pathogenesis, and Emerging Treatment Strategies - Hasan, Saikat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2023.